Application of a cost-benefit model to evaluate the investment viability of the small-scale cogeneration systems in the Portuguese context - Ferreira, Ana Cristina; Teixeira, Senhorinha; Teixeira, José C.F.; Nebra, Silvia A. (International Journal of Sustainable Energy Planning and Management, 2021)
Increasingly, modern society is dependent on energy to thrive. Remarkable attention is being drawn to high energy-efficient conversion systems such as cogeneration. World energy sustainability depends on the rational use of energy, fulfilling the demands without compromising the future of energy supply. The market trends foresee the use of decentralized production and the increasing replacement of conventional systems by small-scale cogeneration units as solutions to meet the energy needs of the building sector. Analysing the influence of the variables that determine the economic viability of decentralized energy production systems has become more important given the scenario of energy dependence and high energy costs for the final consumer. A cost-benefit model was developed and presented to identify the potential of small commercial scale cogeneration systems in the Portuguese building sector, based on cost-benefit analysis methodology. Five case-scenarios were analysed based on commercial models, using different technologies such as internal combustion engines, gas turbines and Stirling engines. A positive value of CBA analysis was obtained for all the tested cases, however, the use of classic economic evaluation criteria such as the net present value, internal rate of return and payback period results led to different investment decisions. The model also highlights the influence of energy prices in the economic viability of these energy power plants. The inclusion of subsidized tariffs for efficient energy production is the most contributing aspect in the analysis of the economic viability of small-scale cogeneration systems in the Portuguese building sector. Only in that case, it would be possible for an investor to recover the capital costs of such technology, even if the technical and societal benefits are accounted for.